2022
DOI: 10.1111/pde.15044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of selumetinib on pediatric elephantiasis neuromatosa

Abstract: Elephantiasis neuromatosa (EN) is a rare and extreme form of plexiform neurofibroma in patients with neurofibromatosis type 1 (NF1). EN is often associated with significant morbidity and remains difficult to treat. We present a case of an 11‐year‐old female with NF1 whose thoracolumbar plexiform neurofibroma and lower extremity EN exhibited clinical improvement from treatment with selumetinib, a selective MEK inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…15 Blegen et al reported the beneficial effect of selumetinib in an 11-year-old girl with elephantiasis neuromatosa. 16 With regard to TSC and SWS, drugs primarily targeting the mTOR pathway have been explored. A review by Franz and Krueger concluded that mTOR inhibition by drugs including sirolimus and everolimus could serve as a disease-modifying therapy in TSC.…”
Section: Discussionmentioning
confidence: 99%
“…15 Blegen et al reported the beneficial effect of selumetinib in an 11-year-old girl with elephantiasis neuromatosa. 16 With regard to TSC and SWS, drugs primarily targeting the mTOR pathway have been explored. A review by Franz and Krueger concluded that mTOR inhibition by drugs including sirolimus and everolimus could serve as a disease-modifying therapy in TSC.…”
Section: Discussionmentioning
confidence: 99%